Response to trametinib in recurrent low-grade serous ovarian cancer with NRAS mutation: A case report - Miriam Champer; Devin Miller; Dennis Yi-Shin Kuo (Elsevier, 2019)
Low-grade serous ovarian cancer represents a minority of ovarian cancers and has distinctive features from high grade epithelial ovarian cancer. While less aggressive, in advanced stage they can be poorly chemo-responsive and incur a treatment challenge. Next generation sequencing of tumors has allowed for the potential for targeted therapy in cancer treatment, which can allow for avoidance of traditional cytotoxic chemotherapy. We present a case of a 56 year old female with advanced recurrent low grade serous ovarian cancer found to have NRAS mutation who underwent targeted therapy with trametinib with immediate and sustained disease response. We review the response and toxicity experienced by the patient, as well as treatment for her toxicity. Keywords: Low-grade serous ovarian cancer, Targeted therapy, MEK-inhibitor